2022
DOI: 10.1096/fj.202101555rr
|View full text |Cite
|
Sign up to set email alerts
|

TIMP2 mediates endoplasmic reticulum stress contributing to sepsis‐induced acute kidney injury

Abstract: Tissue inhibitor of metalloproteinase 2 (TIMP2) has been recognized as an important biomarker for predicting acute kidney injury (AKI) because of its involvement in the process of inflammation and apoptosis in septic AKI. Endoplasmic reticulum (ER) stress, a condition of disrupted ER homeostasis, is implicated in multiple pathophysiological processes, including kidney disease. Herein, we investigated the correlation between ER stress and septic AKI and further explored how TIMP2 regulated ER stress‐mediated ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…We further compared expression and pathway activity of kidney injury markers across different segments between Con and AAN groups. Four kidney injury markers Fabp1 ( 43 ), Havcr1 ( Kim1 ) ( 44 ), Lcn2 ( 45 ) and Timp2 ( 46 ) were upregulated in AAN ( Figure 4G ). More importantly, AAN group not only showed upregulation of adult tubular stem cell markers Cd24a ( Cd24 ) and Prom1 ( Cd106 ) ( 44 ), but also reactivated nephron progenitor markers Sall1 ( 47 ) and Pax2 ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…We further compared expression and pathway activity of kidney injury markers across different segments between Con and AAN groups. Four kidney injury markers Fabp1 ( 43 ), Havcr1 ( Kim1 ) ( 44 ), Lcn2 ( 45 ) and Timp2 ( 46 ) were upregulated in AAN ( Figure 4G ). More importantly, AAN group not only showed upregulation of adult tubular stem cell markers Cd24a ( Cd24 ) and Prom1 ( Cd106 ) ( 44 ), but also reactivated nephron progenitor markers Sall1 ( 47 ) and Pax2 ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
“…In lipopolysaccharide (LPS)-induced AKI models, angiopoietin-like protein 3 knockout mice showed alleviated ER stress and apoptosis via the inhibition of the ROS/GRP78/BAX pathway [ 25 ]. Forsythiaside A suppressed ER stress-induced inflammation and apoptosis, thereby suggesting a pivotal role of ER stress in sepsis-induced AKI [ 26 , 27 ]. GRP170, an ER protein regulating the degradation and assembly of the epithelial sodium channel, inhibits UPR and ER stress, which protects against ischemia- and sepsis-induced AKI [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“… 37 On the other hand, lipid peroxidation could up-regulate apoptosis through endoplasmic reticulum stress (ER stress) and induce apoptosis through TRAIL and FAS pathways. 38 , 39 Therefore, the ability to induce the production of ROS could be used as one of the indexes to judge the effectiveness of the sonosensitizer. In this work, we found that SDT mediated by IR-820@NBs could effectively induce the production of ROS and the change of mitochondrial membrane potential.…”
Section: Discussionmentioning
confidence: 99%